2012
DOI: 10.1111/j.1537-2995.2012.03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti seroprevalence in Minnesota blood donors

Abstract: This study provides new data about B. microti seroprevalence in MN blood donors. Possibly because the targeted collection areas were mostly expected to be endemic for the parasite, the observed seroprevalence levels were higher than expected, although the geographic distribution of positive donors did not completely overlap with the distribution of reported clinical cases in MN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
(18 reference statements)
2
24
0
Order By: Relevance
“…Prior studies of B. microti testing in endemic areas using predominantly research IFAs yielded seroprevalence rates of 1.2% to 1.8% in the highly endemic counties of Middlesex and New London, CT, which were also evaluated in this study, and that those rates were stable over 8 years of study . Higher rates (2%) were recently documented in endemic counties of MN using a similar research IFA, with a single PCR‐positive sample identified of 2150 donors tested . The same investigators reported a seroprevalence rate of 2.5% in the two highly endemic counties of CT .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Prior studies of B. microti testing in endemic areas using predominantly research IFAs yielded seroprevalence rates of 1.2% to 1.8% in the highly endemic counties of Middlesex and New London, CT, which were also evaluated in this study, and that those rates were stable over 8 years of study . Higher rates (2%) were recently documented in endemic counties of MN using a similar research IFA, with a single PCR‐positive sample identified of 2150 donors tested . The same investigators reported a seroprevalence rate of 2.5% in the two highly endemic counties of CT .…”
Section: Discussionsupporting
confidence: 54%
“…) is broader (including 26 states) than the locations of the six regional blood centers included in this study. Moreover, the large sample size contributes a sizable amount of data to those already available in the literature 20‐24. This study also includes donor data from nonendemic areas, which have not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this initial study in endemic and nonendemic blood donor populations, the overall rates of EIA seroreactivity were similar to those reported in several previous studies based on IFA methods . A comparison of the sample sets identified as reactive by EIA versus IFA suggests that the two methods detect overlapping, but not identical subsets (corroborated by the kappa value of 0.38, interpreted as “fair” agreement).…”
Section: Discussionsupporting
confidence: 84%
“…Over the past decade the geographic range of B. microti has expanded and more tick and transfusion‐transmitted cases have been documented . In endemic states, donor seroprevalence can be as high as 2%, with incidence ranging from 1 in 604 to 1 in 100,000 cases per RBC units transfused …”
mentioning
confidence: 99%